An Analysis of Chemical Engineering Students’ Needs on Instructional Reading Strategies - Diana, Sri; Rampeng; Bahar (UNIB Press, 2023)
Reading is an important macro skill besides speaking, writing and listening. Reading is a receptive skill, yet it is still essential for success in both academic and in everyday life. Therefore, the study aims at analyzing chemical engineering students’ needs for instructional reading strategies to help them comprehend the text. A qualitative research design was used for this study with quantitative data collection. Data were collected through questionnaires from 60 chemical engineering students and analyzed using descriptive statistics (the interpretations of percentages). The results show that there are seven important reading instructions selected by chemical engineering students (above 90%) that is drawing conclusion, making prediction, identifying cause and effect, distinguishing between facts and opinions, comparing and contrast, identifying the main ideas and identifying supporting details. Chemical engineering students also had favorable attitudes on three other instructional reading strategies that were considered important with the percentage of below 89 percent they are recognizing and interpreting writer’s view, summarizing and drawing conclusions. Based on the analysis of students’ needs, majority of chemical engineering students believe the seven most important instructional reading strategies should be incorporated into the reading materials as reading comprehension activities.